2016
DOI: 10.1016/j.amepre.2015.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Abuse in Childhood or Adolescence and Gestational Diabetes

Abstract: Introduction Early life abuse has been linked to later Type 2 diabetes, but its association with gestational diabetes has not been examined. The aim of this study was to examine the association between childhood and adolescent abuse victimization and risk of gestational diabetes in the Nurses’ Health Study II. Methods Participants were asked about experiences of physical and sexual abuse in childhood or adolescence in 2001 and about history of pregnancy complications in 2009. Mothers of singleton live births… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
0
22
0
3
Order By: Relevance
“…In a recent review, Mason et al reported a 68% higher risk for GDM among pregnant women with histories of physical and sexual abuse compared to women without abuse histories. 17 The authors hypothesized that abuse may lead to chronic elevation of stress hormones and contribute to insulin resistance, resulting in GDM in pregnancy. Despite the increased risk for GDM and hypothesized biological pathways among women with maltreatment histories, no studies, to our knowledge, have examined associations among childhood maltreatment and insulin resistance or regulation of stress response systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, Mason et al reported a 68% higher risk for GDM among pregnant women with histories of physical and sexual abuse compared to women without abuse histories. 17 The authors hypothesized that abuse may lead to chronic elevation of stress hormones and contribute to insulin resistance, resulting in GDM in pregnancy. Despite the increased risk for GDM and hypothesized biological pathways among women with maltreatment histories, no studies, to our knowledge, have examined associations among childhood maltreatment and insulin resistance or regulation of stress response systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, while the life-course perspective of women’s risk for adverse pregnancy events extends from her infancy – possibly before, given the importance of in utero exposures – there is less empirical evidence examining relationships between these early life exposures and a woman’s health later in life during pregnancy. Maternal recall of childhood experiences– in particular adverse experiences such as abuse and neglect – have been associated with adverse birth outcomes (18, 19), excessive gestational weight gain (20), and development of GDM (21), but biological measurements from that time are rare, due in part to the difficulty and infeasibility of decades-long follow-up studies. Widespread implementation of electronic medical records and improvements in quality of electronic vital records allow for data linkage and the creation of analytic cohorts (22) for use in evaluation of longitudinal risk factors in association with adverse reproductive health (23, 24).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the consideration that the onset and course of hypothyroidism is often insidious and may be precipitated by maternal states and conditions that precede pregnancy, we were particularly interested in considering the role of stress exposure from a maternal life course perspective. We selected exposure to childhood maltreatment (CM) as our primary variable of interest for the following reasons: a) CM represents among the most pervasive and pernicious stressors affecting around one third of the general population, with life-long biological, psychological and behavioral consequences (e.g., Heim et al, 2010); b) we and others have previously demonstrated that a woman’s exposure to CM can produce alterations in several features of gestational biology that relate to embryonic/fetal development (Cammack et al, 2011; Mason et al, 2016; Moog et al, 2016; Shea et al, 2007); c) CM exposure has been associated with reduced thyroid activity in the non-pregnant state (Haviland et al, 2006; Machado et al, 2015; Sinai et al, 2014), with thyroid dysfunction in the postpartum period (Plaza et al, 2010; Plaza et al, 2012), and, more generally, with a higher risk of autoimmune disorders (Dube et al, 2009; Goodwin and Stein, 2004); and d) children of women exposed to CM exhibit an increased risk of developing some of the same behavioral disorders that have been observed in children with moderate maternal thyroid dysfunction (Miranda et al, 2013; Rijlaarsdam et al, 2014; Thompson, 2007). In light of these observations, we hypothesized that women exposed to CM may exhibit an increased likelihood of thyroid dysfunction in pregnancy, a time period of particular importance for not only the mother but also for her developing fetus.…”
Section: Introductionmentioning
confidence: 99%